2016
DOI: 10.17532/jhsci.2016.334
|View full text |Cite
|
Sign up to set email alerts
|

Differences in dental caries experience between diabetic adolescents and healthy controls

Abstract: Introduction: While the influence of type 1 diabetes mellitus (T1DM) on periodontal health is well established, results of previous studies regarding the association of this metabolic disease and caries experience are rather inconsistent. The aim of this study was to assess the differences between caries status of healthy and adolescents with T1DM, as well as to determine the differences in caries experience among diabetic patients in relation to their metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations